Conjugation, Prodrug, and Co-Administration Strategies in Support of Nanotechnologies to Improve the Therapeutic Efficacy of Phytochemicals in the Central Nervous System - Giovanna Rassu; Milena Sorrenti; Laura Catenacci; Barbara Pavan; Luca Ferraro; Elisabetta Gavini; Maria Cristina Bonferoni; Paolo Giunchedi; Alessandro Dalpiaz (MDPI AG, 2023)
Phytochemicals, produced as secondary plant metabolites, have shown interesting potential therapeutic activities against neurodegenerative diseases and cancer. Unfortunately, poor bioavailability and rapid metabolic processes compromise their therapeutic use, and several strategies are currently proposed for overcoming these issues. The present review summarises strategies for enhancing the central nervous system's phytochemical efficacy. Particular attention has been paid to the use of phytochemicals in combination with other drugs (co-administrations) or administration of phytochemicals as prodrugs or conjugates, particularly when these approaches are supported by nanotechnologies exploiting conjugation strategies with appropriate targeting molecules. These aspects are described for polyphenols and essential oil components, which can improve their loading as prodrugs in nanocarriers, or be part of nanocarriers designed for targeted co-delivery to achieve synergistic anti-glioma or anti-neurodegenerative effects. The use of in vitro models, able to simulate the blood-brain barrier, neurodegeneration or glioma, and useful for optimizing innovative formulations before their in vivo administration via intravenous, oral, or nasal routes, is also summarised. Among the described compounds, quercetin, curcumin, resveratrol, ferulic acid, geraniol, and cinnamaldehyde can be efficaciously formulated to attain brain-targeting characteristics, and may therefore be therapeutically useful against glioma or neurodegenerative diseases.